Malay bureaucracy in Japanese administration: Japanese Expectations, Malay Dilemmas and Problems - Fathil, Fauziah (Universiti Malaya Press, 2015)
Following the Japanese occupation of Malaya, a military administration was established. Led by Japanese military officers, the new administration was assisted by the existing local bureaucracy or administrative machinery of which the Malays were the majority. The expectation of the Japanese authority i.e. the locals to render full cooperation and loyalty and not to oppose Japanese rule had placed the Malay bureaucrats in a tight position. Having to serve the Japanese masters put the Malay civil officers in a dilemma and caused them to endure some problems. Their reluctance to render cooperation would be seen as an unfaithful act liable to be punished or, worse still, given the multi-racial composition of the Malayan society, might result in the Malays as a group losing their special rights or positions to non-Malays. Yet, to work for the Japanese entailed unwanted perceptions or reactions from among their fellow countrymen that they were seen as collaborators of the Japanese or traitors of their own country. Based primarily on library research, this paper aims to analyze the difficult position of the Malay bureaucrats or civil servants during the war years and the kind of problems and troubles that they were facing from the Japanese and their fellow countrymen alike, particularly, the anti-Japanese Malayan Chinese. Japanese expectations and reasons for their recruitment of Malays as administrators in the first place will also be examined. Finally, the findings will highlight that whatever was experienced by the Malay bureaucrats during these years partly contributed to the rise of Malay nationalism in the years that followed the end of the Japanese occupation in 1945.